Stability-and-Peace Accelerator: country cases for Nigeria, Kenya and Jordan - Ahmed, D.; Karunakaran, K.; Qiu, Z.; Al-Zu’bi, Maha; Michalscheck, Mirja; Kamanda, Josey; Quadri, S.; Nkosi, Mahlatse; Craparo, A. (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The Stability and Peace Accelerator (SAPA) Program was implemented by the World Food Programme’s Innovation Accelerator and in collaboration with International Water Management Institute (IWMI), the Alliance of Biodiversity International and the International Center for Tropical Agriculture (CIAT), and the International Institute for Tropical Agriculture (IITA), with support from the CGIAR Initiative on Fragility, Conflict, and Migration1 . The SAPA program focused on identifying and supporting the scaling of potentially high-impact innovations that bolster resilience of food, land, and water systems (FLWS) in Fragile and Conflict Affects (FCA) settings.